The current landscape of formative assessment and feedback in graduate studies: a systematic literature review - Solis Trujillo, Beymar Pedro; Velarde-Camaqui, Davis; Gonzales Nuñez, Cristhian Anibal; Castillo Silva, Estela Vicenta; Gonzalez Said de la Oliva, Mariela del Pilar (Frontiers in Education, 2025)
Formative assessment has evolved into a comprehensive approach for enhancing student learning across academic levels, yet gaps remain regarding its impact on graduate students with diverse needs. This study conducts a systematic literature review (SLR) of empirical research published between 2014 and 2024, analyzing 188 initial articles retrieved from Scopus and Web of Science, which were narrowed down to 19 eligible studies. The aim is to examine how formative feedback influences the learning and motivation of graduate students. The results indicate that: (a) immediate and specific feedback enhances academic performance and promotes self-regulation, empowering students to manage their learning processes more effectively; (b) technological tools facilitate personalized and accessible feedback, tailoring learning experiences to individual needs; and (c) the implementation of feedback strategies that consider individual differences contributes to greater equity and effectiveness in graduate education. This study not only addresses gaps in the literature by synthesizing evidence on formative assessment but also highlights the transformative role of technology and personalized strategies in promoting autonomous and meaningful learning in graduate programs.